1993
DOI: 10.1111/j.1600-0714.1993.tb00041.x
|View full text |Cite
|
Sign up to set email alerts
|

Microradiography and light microscopy of mineralization in the pulp of undemineralized human primary molars

Abstract: This study was undertaken to investigate the prevalence, location and histologic features of the different types of mineralization observed in the pulp of human primary molars. Microradiography and light microscopy of undemineralized material disclosed that 95% of primary molars contain pulp calcifications. Histologically, their structure may be classified into four different types: (1) pulp stones, (2) diffuse calcifications, (3) eburnoid tissue and (4) spherulitic calcifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
5

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 7 publications
3
40
0
5
Order By: Relevance
“…The detection of pulp stones on dental radiographs is possible when pulp stones are larger than 200 µm in diameter; therefore, very small pulp stones cannot be seen on radiographs. 1,4,8,10,[13][14][15][16] The prevalence of pulp stones in the examined teeth of this research was 9.6%. They were found to be more prevalent in the maxillary arch, especially in the first and second molars.…”
Section: Discussionmentioning
confidence: 98%
“…The detection of pulp stones on dental radiographs is possible when pulp stones are larger than 200 µm in diameter; therefore, very small pulp stones cannot be seen on radiographs. 1,4,8,10,[13][14][15][16] The prevalence of pulp stones in the examined teeth of this research was 9.6%. They were found to be more prevalent in the maxillary arch, especially in the first and second molars.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, Arys et al, [20] found that age did not have any influence on the occurrence of pulpal calcifications. They examined 42 primary molars and their results revealed that pulp stones were present in 78% of the molars, with 95% of the material showing some form of pulpal calcification.…”
Section: Primary Teeth and Pulp Stonesmentioning
confidence: 90%
“…Alguns estudos apontam a cárie dentária como um dos possíveis fatores de formação de nódulos pulpares, pois o processo carioso induz a formação de dentina terciária, para que esta possa proteger a polpa dentária dos produtos tóxicos produzidos pelas bactérias cariogênicas. Ainda, esses mesmos produtos tóxicos podem desencadear um processo de irritação crônica ao tecido pulpar, que reage com a formação de nódulos pulpares 4,5,9 . No presente estudo, não foi possível verificar associação entre a presença de cárie dentária e nódulos pulpares (p = 0,757), resultado que se deve, provavelmente, ao baixo índice de lesões de cárie encontrado.…”
Section: Discussionunclassified
“…A presença de restaurações é considerada um possível fator para o surgimento de nódulos pulpares, na medida em que o procedimento operatório, restaurador e o material utilizado podem ser irritantes para a polpa, estimulando o surgimento desses nódulos 4,5,9 . Uma das hipóteses do presente estudo foi a de que o bruxismo, por causar estresse oclusal e desgaste dentário, levaria à irritação do tecido pulpar, podendo culminar com a indução da formação de nódu-los.…”
Section: Discussionunclassified
See 1 more Smart Citation